Margin-Controlled, Staged Surgical Excision in the Treatment of High-Risk Basal Cell Carcinomas of the Head and Neck Region - SALMAN, ANDAÇ; DURMUŞ KOCAASLAN, FATMA NİHAL; BAYRAMİÇLİ, MEHMET NURİ ÜMİT (SAGE PUBLICATIONS INC, 2019)
Background: The most common skin cancer is basal cell carcinoma (BCC), and the gold-standard treatment for high-risk tumours is Mohs surgery. However, alternative methods are needed for high-risk tumours in countries where the performance rate of Mohs surgery is low. Objectives: The objective of this article is to investigate the feasibility, efficacy, and safety of margin-controlled, staged surgical excision (MCSSE) in high-risk tumours as a possible treatment alternative. Methods: A retrospective cohort study, including patients diagnosed with high-risk BCC in the head and neck region and treated with MCSSE between 2003 and 2010, was conducted. Results: During the study period 50 tumours in 47 patients were treated, with low adverse event rates and high patient satisfaction rates. Of the 50 tumours, 1 recurred at the 12-month follow-up. Conclusions: Despite the small sample size and relatively short follow-up period, the present study shows that MCSSE might be a feasible alternative for the treatment of high-risk BCCs in institutions where Mohs surgery is not performed. Future studies on long-term recurrence rates are needed.
Keywords: Basal cell carcinoma; high risk; margin-controlled; staged surgical excision; MOHS SURGERY; FOLLOW-UP; SLOW MOHS